OK first convert one of the equations into Y=MX+b form
Y-2x = 3
Add 2X
Y = 2x +3
Now substitute this equation in the other one.
So it would be
3X - 2Y = 5
3X-2(2x+3) = 5
Now solve for y
3X - 4X - 6 = 5
-1X - 6 = 5
Add 6
-1X = 11
X = -11
Now substitute this into one of the equations
Y - 2X = 3
Y -2(-11) = 3
Y +22 = 3
y = 3-22
y = -19
14 because i did the math and i was right
I believe the correct answer is he paid the right amount
You would multiply the cups of flour by 3 and the cups of water by 3. which would give you 9 cups of flour and 6 cups of water. the ratio is 1.5 cups of flour to 1 cup of water.